Efficacy and Safety of Regdanvimab (CT-P59): A Phase 2/3 Randomized, Double-Blind, Placebo-Controlled Trial in Outpatients With Mild-to-Moderate Coronavirus Disease 2019. (2nd February 2022) - Streinu-Cercel, Anca; Săndulescu, Oana; Preotescu, Liliana-Lucia; Kim, Jin Yong; Kim, Yeon-Sook; Cheon, Shinhye; Jang, Young Rock; Lee, Sang Joon; Kim, Sung Hyun; Chang, Ilsung; Suh, Jee Hye; Lee, Seul Gi; et al.
Abstract: Background: Regdanvimab (CT-P59) is a monoclonal antibody with neutralizing activity against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). We report on part 1 of a 2-part randomized, placebo-controlled, double-blind study for patients with mild-to-moderate coronavirus disease 2019 (COVID-19). Methods: Outpatients with mild-to-moderate COVID-19 received a single dose of regdanvimab 40 mg/kg (n = 100), regdanvimab 80 mg/kg (n = 103), or placebo (n = 104). The primary end points were time to negative conversion of SARS-CoV-2 from nasopharyngeal swab based on quantitative reverse transcription polymerase chain reaction (RT-qPCR) up to day 28 and time to clinical recovery up to day 14. Secondary end points included the proportion of patients requiring hospitalization, oxygen therapy, or mortality due to COVID-19. Results: Median (95% CI) time to negative conversion of RT-qPCR was 12.8 (9.0–12.9) days with regdanvimab 40 mg/kg, 11.9 (8.9–12.9) days with regdanvimab 80 mg/kg, and 12.9 (12.7–13.9) days with placebo. Median (95% CI) time to clinical recovery was 5.3 (4.0–6.8) days with regdanvimab 40 mg/kg, 6.2 (5.5–7.9) days with regdanvimab 80 mg/kg, and 8.8 (6.8–11.6) days with placebo. The proportion (95% CI) of patients requiring hospitalization or oxygen therapy was lower with regdanvimab 40 mg/kg (4.0% [1.6%–9.8%]) and regdanvimab 80 mg/kg (4.9% [2.1%–10.9%]) vs placebo (8.7% [4.6%–15.6%]). No serious treatment-emergent adverse events or deaths occurred. Conclusions: Regdanvimab showed a trend toward a minor decrease in time to negative conversion of RT-qPCR results compared with placebo and reduced the need for hospitalization and oxygen therapy in patients with mild-to-moderate COVID-19. Clinical trial registration. : NCT04602000 and EudraCT 2020-003369-20 .